Vielfältige Lösungsstrategien von Kindern bei Aufgaben zum räumlichen Denken (mathematica didactica, 2013)
The presented study focuses on spatial tasks and the variety of solution strategies fourth grade children used. In guideline-based interviews four groups of tasks were presented which were constructed on the model of MAIER (1999). The answers of the children were structured with a qualitative strategy analysis. Traditionally it is assumed, that due to the structure of the task special strategies are intended. The results show that children use even more and multifarious strategies than expected. Additionally, they showed combinations of strategies in every group of tasks.